Technique to open an ampoule with an “Ampoule Opener” tool - Rahayu, Pujen Tri; Asmiati, Dewi; Santosa, Agus (MEDISAINS, 2020)
Background: The incidence of scratched by ampoule fragments while preparing medicine could harm the nurse. It needs specific tools and techniques that are effective to minimize scratches when opening an ampoule.Technique: We compared a manual ampoule opening technique and another using a unique tool, the "ampoule opener" developed by research. The trial was carried out on 100 nurses in the health science faculty laboratory of the Muhammadiyah University of Purwokerto and at the Ajibarang Hospital. The safety and convenience variables were assessed to determine the effectiveness of the two techniques. The results showed that using the ampoule opener was proven to be more comfortable and safer from several techniques tested.Conclusion: The technique of opening the ampoule using the ampoule opener proved to be more comfortable and safer for a nurse.